Oral Health Status of Mississippi Delta 3- to 5-Year-Olds in Child Care: An Exploratory Study of Dental Health Status and Risk Factors for Dental Disease and Treatment Needs - Linda H. Southward, PhD; Angela Robertson, PhD; Elisabeth Wells-Parker, PhD; (Blackwell Synergy, 2006)
For poor and minority young children, disparities exist in dental health and treatment. In rural impoverished areas, institutions that reach young children and potentially offer access to care are limited.